Lithic Technology in the Middle Potomac River Valley of Maryland and Virginia - Hranicky, Wm Jack (Springer US, 2002)
The archaeological focus on a single geographical area offers an opportunity to present projectile point typology as a microtechnology even though some of the types have widespread distributions. The area of the Middle Potomac River Valley presents a physical artefact collection for a view of prehistory. This volume, which includes several hundred images of the investigation, artefacts and archaeological research compiled and recorded from over 30 years of work in the area, includes: -an overview of the Middle Potomac River Valley archaeology including the peoples and sites; -new data and interpretations for the lithic technology of the area; and -classification and typology of artefacts including the usage of projectile point, axe, celt, drill, and knife implements. This work will be of great interest to prehistory archaeologists, especially those working in the Middle Atlantic region of the United States.